Microcantilever Fracture Tests on Eutectic NiAl–Cr(Mo) In Situ Composites. Issue 6 (3rd March 2021) - Gabel, Stefan; Giese, Sven; Merle, Benoit; Sprenger, Ioannis; Heilmaier, Martin; Neumeier, Steffen; Bitzek, Erik; Göken, Mathias
Abstract : Lamellar eutectic NiAl–Cr(Mo) alloys show an increased fracture toughness due to different toughening mechanisms. These mechanisms result from the fibrous or lamellar microstructure of the two constituting phases α‐Cr(Mo) and β‐NiAl. However, the fracture toughness of the individual phases and the evolution from early crack growth to the toughening mechanisms have not yet been systematically studied. Herein, bending tests on focused ion beam (FIB)‐notched microcantilever beams are used to characterize the small‐scale fracture properties. The micromechanical investigations reveal that the fracture toughness of the α‐Cr(Mo) phase ( 7.5 − 9.1 MPa m ) is much higher than the fracture toughness of β‐NiAl ( 2.2 − 2.9 MPa m ). Larger cantilevers in the crack arresting orientation show an enhanced fracture toughness with up to 14.4 MPa m, which is still lower than the one of macroscopic experiments. This is attributed to the small interaction volume of the crack, which hinders the full exploitation of potential extrinsic toughening mechanisms. Abstract : The influence of the Mo addition on the fracture toughness in NiAl–Cr eutectic alloys is measured on the microscale. The measurements reveal that the Mo addition has only a small impact on the fracture toughness of the two phases. The overall fracture toughness of the system is mainly influenced by the toughening mechanisms and the size of the lamellae.